2019
DOI: 10.5840/ijpp2019511
|View full text |Cite
|
Sign up to set email alerts
|

An Existential Perspective on Addiction Treatment

Abstract: In this essay I argue that an adequate understanding of addiction and its recovery should be informed by an existential understanding of human nature. I provide a brief overview of an existential perspective/foundation of addiction and recovery, which will contextualize the remainder of the essay. I then present a case study of how the six-step philosophical practice method of Logic-Based Therapy can assist with issues that often arise in addiction treatment framed through an existential perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…approach allows individuals to search for meaning, have a purpose, and create a positive relationship with psychological factors. It gives them more adaptation ability, life satisfaction, and psychological well-being [20]. The effectiveness of this method has been confirmed in various cases [21].…”
Section: Plain Language Summarymentioning
confidence: 91%
“…approach allows individuals to search for meaning, have a purpose, and create a positive relationship with psychological factors. It gives them more adaptation ability, life satisfaction, and psychological well-being [20]. The effectiveness of this method has been confirmed in various cases [21].…”
Section: Plain Language Summarymentioning
confidence: 91%
“…12 This article has the secondary purpose of also highlighting the utility of LBT for addiction recovery, as I have argued elsewhere. 13 I explore how LBT can shape a philosophically oriented recovery pathway for individuals in addiction recovery. 14 I have previously suggested that PWL can be a compelling, and legitimate recovery pathway for individuals in addiction recovery, as one of many recovery pathways.…”
Section: Friedrich Nietzsche -Thus Spoke Zarathustramentioning
confidence: 99%
“…From a psychodynamic and needs perspective addictive behaviour can be understood as directed at meeting ontological needs, but what differentiates addictive behaviour from other responses (or other satisfiers) is that it paradoxically destroys the individual's capacity to meet the need (s) it is attempting to satisfy, as well as the capacity to meet other needs. As an addictive lifestyle progresses, the individual's capacity to have most of his or her needs met becomes diminished, until there is an almost total reliance on the substance or behaviour to meet these needs (Du Plessis, 2014, 2018.…”
Section: I Robotmentioning
confidence: 99%